The conflict between the WTO agreements and MEAs : a special reference to the reconciliatory efforts of the Committee of Trade and Environment (CTE) - Sackor, Ahmad S. (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
This thesis analyses the reconciliatory process of the Committee of Trade and Environment (CTE) under the WTO. As it is observed, one of the stranded issues at both the academic and political arenas is the attempt to attain a possible integration and incorporation of trade and environmental values in a single paradigm. Trade liberalisation and environmental protection ostensibly play a huge part in achieving sustainable development. Despite this important role-play, they are both considered totally apart due to their distinct in-root policies. This disparity has created a serious perception that the two sides are incompatible with different objectives. However, efforts from trade and the environment sides have finally overturned this untenable notion by acknowledging the possibility of the two sides being reconciled. Among these relentless efforts is the initiative to establish the committee on trade and Environment (CTE) as a forum where trade-environmental issues can be debated. The CTE since its establishment in 1995 has been working precisely on how the linkage between the World Trade Organisation (WTO) and Multilateral Environmental Agreements (MEAs) could be defined. It has been a difficult task for the CTE to complete which is due to the numerous complexes and multifaceted constraints that have kept it at bay from reaching further closer to achieving its objectives. One of the principal reasons of trade-environmental complexity is that the policy objectives of trade and the environment have been discussed differently and isolated from the sustainable development context. The fact that the CTE has not yet been able to effectively deliver what was anticipated from it had never faded hopes of trade-environmental debates from being a possible dream. But the pace development seen in both fields has arisen the need to find a congruity between the two policies. In this way, several suggestions have been put on the negotiation table. Among the proposed suggestions include the amendment of some relevant WTO provisions. In addition to that, there is also a view of including some environmental experts in the WTO judicial exercises in cases that involve trade-restrictive measures set out in MEAs. But these proposals have not received greater supports especially from the WTO's developing and least-developed country Members. The findings of the research draw up the conclusion there is a potential conflict between trade and environmental laws which had required swift addressing mechanisms. Thus series of attempt to reconcile, the research reveals that the reconciliatory efforts in the CTE have been very slow and latent because it workloads have been overstressed and expanded linking it to other negotiating committees, which makes it extremely difficult in practical to narrow areas of consensus. The outcome of this had made CTE's negotiations inactive in that, there has been too much paper works without any practical effects. As a way to avoid this policy conundrum, the researcher urges all negotiating parties to make some sacrifices by settling their differences and work collectively so for achieving the sustainable development known as the triple win solution. This solution strives to balance between economic and social growth alongside with environmental protection. As regard to the methodology used, the research did not conduct any interview with CTE Members because of the intense politic involved and the sensitivity of this matter. Therefore the researcher largely depends on the WTO Members views and suggestions circulated within the CTE database that are critically evaluated for concrete reconciliatory outcome.